Decreased expression of microRNA-26b in locally advanced and inflammatory breast cancer - Ding, Qingqing; Wang, Yan; Zuo, Zhuang; Gong, Yun; Krishnamurthy, Savitri; Li, Chia-Wei; Lai, Yun-Ju; Wei, Wei; Wang, Jing; Manyam, Ganiraju C.; Diao, Lixia; Zhang, Xinna; et al. (Human pathology, 2018)
Advanced-stage breast cancer patients comprise a smaller proportion of breast cancer patients than do early stage patients and are more likely to experience a poor outcome. Understanding the underlying molecular mechanisms and identifying new biomarkers for treatment in this subgroup of patients is paramount. With the aim of identifying microRNAs that are regulated in advanced-stage breast cancer, we found lower expression of miR-26b, a member of the miR-26 family, in inflammatory breast cancer and noninflammatory locally advanced breast cancer tissue than in normal breast tissue, by quantitative real-time polymerase chain reaction and in situ hybridization. Quantitative real-time polymerase chain reaction (but not in situ hybridization) also revealed lower miR-26b expression in inflammatory breast cancer than in noninflammatory locally advanced breast cancer. Furthermore, lower expression of miR-26b was correlated with shorter distant metastasis–free survival and overall survival in univariate analysis, and with shorter overall survival in multivariate analysis. The expression of miRNA-26b was inversely associated with EZH2 protein expression in several breast cancer cell lines, and overexpression and knockdown of miR-26b caused corresponding changes in EZH2 expression. Our study shows that miR-26b may regulate EZH2 expression in breast cancer and may be useful as a therapeutic target for inflammatory breast cancer and noninflammatory locally advanced breast cancer. •Expression of miR-26b is lower in inflammatory breast cancer by quantitative PCR.•miR-26b is lower in breast cancer than normal tissue by in situ hybridization.•Lower expression of miR-26b is associated with worse survival.•miR-26b may regulate EZH2 protein expression in breast cancer.